The effect of core stability training on ball-kicking velocity, sprint speed, and agility in adolescent male football players - Sofuoglu, Ceyda; Topcu, Zehra Guchan; Tunay, Volga Bayrakci (Public Library Science, 2024)
This study was conducted to investigate the effect of core stability training program on ball-kicking velocity, running speed, and agility in adolescent male football players. To this end, 36 male football players aged 12-14 were divided into the training group and control group. Before implementing the core stability training program, participants' ball-kicking velocity, sprint speed, and agility performance were measured with a Bushnell velocity radar gun, 20 m sprint test, and 505 agility test, respectively, in both training group and control group. After the measurements, the training group followed core stability training program three days a week, for eight weeks in addition to the routine training program, while the control group followed the routine training program only. Ball-kicking velocity, sprint speed, and agility performance were re-measured in both groups after the completion of the core stability training program. Significant improvements were detected in all parameters, i.e., ball-kicking velocity, sprint speed, and agility performance in the training group (p<0.05). On the other hand, in the control group, no significant change was detected in the ball-kicking velocity and sprint speed (p>0.05), whereas a significant improvement was observed in agility performance (p<0.05). Inter-group comparisons revealed statistically significant differences between the groups in ball-kicking velocity and sprint speed in favor of the training group (p<0.05), while no significant difference was found between the groups in agility performance (p>0.05). In conclusion, this study's findings suggest that core stability exercises can be incorporated into the routine training program of adolescent male football players.
Keywords: Soccer; Performance; Strength; Endurance; Injuries; Fitness; Balance